Influence of Slat Size Variation as Passive Flow Control Instruments on NACA 4415 Airfoil Toward Aerodynamic Performance - James Julian; Rizki Aldi Anggara; Fitri Wahyuni (Institut Teknologi Sepuluh Nopember, 2023)
Airfoil is a fundamental geometry in designing various aerodynamic objects. Passive flow control installation is essential in determining the airfoil's aerodynamic performance. The influence of variations in slat size as a passive flow control instrument is analyzed using the CFD method with a Reynold number of Re= 10^6. NACA 6641 airfoil was used as the slat geometry with size variations of 10%c and 16%c. Based on the computational results, variations in slat size have a substantial influence on the aerodynamic efficiency of the airfoil. Variations in slat size additional Cl ability to reach 20.6043% and 13.1917%, respectively. In addition, a 16%c slat can delay a stall until it reaches AoA ≥ 19°. Meanwhile, a 10%c slat can delay a stall until it reaches AoA ≥ 17°. However, variations in slat size also affect the resulting drag force. Slat measuring 16%c can addition Cd up to 50.9252%. Meanwhile, 10% c slat additional Cd up to 21.8389%. Based on the resulting lift-to-drag ratio curve, a 10%c slat has the lowest lift-to-drag ratio compared to a 16%c slat. However, a 10%c slat has the highest level of stability when compared to a 16%c slat installation and without a slat installation.